Syntheses of (6S)-cephalosporins from 6-aminopenicillanic acid - Fekner, T; Baldwin, J; Adlington, R; Jones, T; Prout, C; Schofield, C (2000)
Two practical routes to (6S,7S)-cephalosporins from 6-aminopenicillanic acid (6-APA) are described. In the first, 6-APA was converted to (2S,4S,5S,6S)-penicillin sulfoxide 49, which underwent Morin ring expansion to a protected (6S,7S)-cephem 50. In the second, ester 15 was converted to (2S,4S,5S,6R)-penicillin sulfoxide 58, which was then transformed into (6S,7R)-cephem 59. Different methods for the epimerisation of the C-7 position of cephem 59 were examined. (C) 2000 Elsevier Science Ltd.